Evaluation of a novel inactivated vaccine against duck circovirus in muscovy ducks - Zhaolong, Li; Guanghua, Fu; Zhihua, Feng; Jianhua, Chen; Shaohua, Shi; Rongchang, Liu; Longfei, Cheng; Hongmei, Chen; Chunhe, Wan; Yu, Huang (Veterinary microbiology, 2020)
•An inactivated DuCV vaccine was developed using PBMC culture medium in vitro.•The inactivated DuCV vaccine induced efficient systemic immune responses.•This DuCV vaccine enhanced protective immune responses against DuCV infection. Duck circovirus (DuCV), an immunosuppressive pathogen, causes serious damage to waterfowls worldwide. A highly efficient vaccine would play a crucial role in preventing DuCV infections in the waterfowl breeding industry. However, to date, there is a dearth of commercial vaccines owing to the lack of a cell culture system for propagating the requisite virus amounts in vitro. In this study, we isolated DuCVs from Muscovy ducks, helped them proliferate using peripheral blood mononuclear cells (PBMCs), and developed an inactivated vaccine. Muscovy ducks vaccinated with the inactivated vaccine had higher neutralizing antibody titers than the control ducks and higher protection in the challenge experiment (as assessed by weight measurement). Moreover, the inactivated vaccine did not cause feather abnormalities, growth repression, and dwarf syndrome; likewise, lesions and lymphocyte apoptosis in the bursa of Fabricius, spleen, and thymus were not observed. Significantly lower virus shedding from the inactivated vaccine was detected up to 42 days post-inoculation. Together, these results suggest that the inactivated DuCV vaccine can induce a high immune response, is relatively safer for Muscovy ducks, and thus it is a protective vaccine candidates against DuCV infection.